Synthesis of Biologically Important Chiral Morpholine Derivatives (Bangladesh Journal of Scientific and Industrial Research, 2007)
Electrophile (Br2) induced cyclization of optically pure N-allyl-?-aminoalcohols 1a, 1b, 1c and 2a, 2b gave chiral morpholines (2R, 5S)- 3a, 3b, 3c and (2S, 5R)- 4a, 4b respectively. Quenching of the reaction with Na2CO3 after 5 min afforded 60 % conversion with 100 % de, whilst a 2:1 mixture of two diastereomers was obtained upon complete conversion. However, electron donating substituent (OMe) on the para position of the C-2 aryl moiety (substrates 1b and 2b) accelerates the reaction to give 80 % conversion and 50 % isolated yield of single diastereomer after 5 min and 8:1 mixture of diastereomers on complete conversion after 10 min. Bangladesh J. Sci. Ind. Res. 42(2), 135-146, 2007